A Two-Country Questionnaire Study of Biomedical Student Opinions Regarding Online Teaching During COVID-19 - Irena Ognjanovic; Irina Yakushina; Elena Shustikova; Maria Mikerova; Vladimir Reshetnikov; Sara Mijailovic; Jelena Nedeljkovic; Dragan Milovanovic; Ljiljana Tasic; Vladimir Jakovljevic; Tamara Nikolic Turnic (Epidemiologia)
Background: The purpose of this study was to compare the opinions of biomedical students from Russia and Central Serbia about learning methods in the time of the COVID-19 pandemic. Methods: This is a comparative questionnaire study that used the validated questionnaire tool eMedQ, conducted via the online platform Anketolog.ru from February to May 2022 at Sechenov University and the University of Kragujevac in the same period. At Sechenov University, 694 students took part in the survey, while at the University of Kragujevac, the total number of participants was 209. The eMedQ questionnaire, in Russian and Serbian, consists of 45 closed-ended questions with 7 domains: demographic characteristics, experience with online teaching, education process (teaching organization), aspects of mental functioning, clinical skills, technical aspects, and quality of life. Results: During the COVID-19 lockdown, in Serbian and Russian biomedical faculties, we observed the high flexibility of Russian students with greater experience when it comes to online education before the pandemic compared to students from Serbia. Also, the Russian students declared that they were strongly motivated to achieve clinical skills and to learn, while a larger number of Serbian students reported disrupted mental functioning and learning problems. Conclusions: At the time of isolation, at Serbian and Russian biomedical faculties, we noticed the higher flexibility of Russian students with more experience than students from Serbia. Also, the Russian students declared that they were strongly motivated both to acquire clinical skills and to learn, while a larger number of Serbian students reported reduced mental functioning and learning problems.